Safety and efficacy of a modified endoscopic full-thickness resection technique for gastric submucosal tumors: a case series - Zhou, Yingsheng; Huang, Yan; Cheng, Wen; Wang, Jiamin; Liu, Xiaoqiang; Peng, Huan; Zhang, Juan; Feng, Qiaoqun (Frontiers in Oncology, 2024)
Objectives: Endoscopic full-thickness resection (EFTR) has proven effective and economical for patients with gastric submucosal tumors (SMTs). However, the poor operative field of view, the risk of massive haemorrhage and the difficulties in defect closure, have limited its widespread application. Herein, we described a modified EFTR technique aimed at simplifying both the dissection and defect closure procedures by using common and economical endoscopic accessories.Methods: Sixteen patients who underwent the modified EFTR for gastric SMTs in the Shenzhen Guangming district People's Hospital were enrolled in the case series. Following a cross incision to expose the intraluminal surface of tumor, the tumor was captured by suction through a transparent cap and the root was ligated using a loop. The tumor and part of the suction tissue were removed along the ligated root. Then, a tension-relieving closure was performed by clipping the raised plica in four quadrants outside the ligated root. Patients' demographics, tumor characteristics, and therapeutic outcomes were evaluated retrospectively.Results: All tumors had an R0 resection. The median procedure time was 40.5 min (IQR 35.12-50.13). No severe perioperative adverse events occurred. No residual lesion or recurrence was reported during the follow-up period of 6.5 months (IQR 5.10-10.02).The safety and practicability of the modified technique might allow for wide clinical applications of Modified-EFTR in micro-gastric SMTs.